The Reintegration of victims of human trafficking: Approaches and Practices in Nepal (The Journal of Knowledge and Innovation, 2023)
This research paper tries to analyze the shelter services and care supports to reintegrating the victims of human trafficking at the family and community level. Primarily, the study applied the qualitative approach by adopting both primary and secondary sources of information. For substantiating secondary information, 40 qualitative in-depth and key informant interviews were conducted. It was found that priorities of shelters are crucial for providing composite and comprehensive services for sustainable and dignified reintegration of victims of trafficking. The shelter care and services mainly orient to victim-centric approach to provide composite service package to victims. Immediate, short-term and long-term services play crucial role for successful reintegration in family and community. The multiple packages in shelter's lone effort was observed to be the best for delivering the best care and services. The widely applied approach of shelters was found victim centered approach, shelter based approach and the community approach. Among these approach, shelter based comprehensive service oriented approach found suitable for sustainable and dignified reintegration of victims of trafficking.